Synovial chondromatosis as an etiology of ankle impingement: a case report - Souza Júnior, Eli Ávila (Journal of the Foot & Ankle, 2021)
Anterior ankle impingement is a common cause of chronic pain in this site and has synovial chondromatosis, albeit rare, as one of its possible etiologies. Both arthroscopic approach and open arthrotomy are reported as therapeutic option, but the few published data showed that the first is believed to bring more advantages. In a recent study, one of the limitations found by the authors was the rareness of this condition in the ankle, and thus the small number of publications on the topic. We present the rare case of synovial chondromatosis of the ankle in a middle-aged man, which was clinically manifested as anterior impingement syndrome and treated arthroscopically, showing an atypical arboriform vascularization pattern. Level of Evidence V; Diagnostic Studies; Expert Opinion.